Simulation of a Marl Rock Slope Failure Parallel to the Nalut Mountain Road, Libya - Ali Mansur; Aboalgasem Alakhdar (AlQalam Journal of Medical and Applied Sciences, 2025)
In March 2021, a sudden rockfall occurred on the Nalut mountain road, resulting in the closure of this critical transportation route. Notably, the failure took place in the absence of rainfall or other conventional external triggers. This study aims to simulate the failure mechanism and assess the key structural factors contributing to slope instability by integrating field investigations with numerical modeling using RocPlane software. The analysis revealed that the affected slope comprises weak marl rocks and that the dominant factor in the failure was the presence of discontinuity sets, particularly Set 2 and Set 3, inclined at 45°, which intersected with the slope direction and formed a kinematically unstable wedge. This wedge was further facilitated by horizontal joints (Set 4 at 0°), creating conditions for complete structural failure. All discontinuity sets recorded a safety factor of zero, reflecting total instability. The driving force in Sets 2 and 3 was approximately 30.34 t/m, with wedge weights ranging from 42.90 to 48.43 t/m. These findings confirm that internal rock structure, rather than external environmental factors, was the primary cause of the failure. The study recommends reducing slope angles below 45°.